2013
DOI: 10.3844/ajessp.2013.310.316
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH PERFORMANCE, BIOMASS AND PHYTOEXTRACTION EFFICIENCY OF <i>ACACIA MANGIUM</i> AND <i>MELALEUCA CAJUPUTI</i> IN REMEDIATING HEAVY METAL CONTAMINATED SOIL

Abstract: Heavy metals are very toxic and soil contaminated with sewage sludge urgently need remediation in order to avoid related health hazards. Phytoremediation is a low cost and reliable technique to remediate heavy metal contamination. However phytoremediation using timber species was rarely reported and its efficiency was questionable. A field study was conducted to examine the efficiency of two timber species namely Acacia mangium and Melaleuca cajuputi in phytoextraction of Zn, Cu and Cd from contaminated soil. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
3
11
0
4
Order By: Relevance
“…It is also plant owing to its remarkable capacity to extract metal from polluted soils. The phytoremediation potential of A. mangium was been previously reported in numerous studies (Majid et al, 2012;Mohd et al, 2013). In fact, Majid et al (2012) demonstrated that A. mangium can accumulate 93.5 mg kg -1 of copper (Cu) and 79 mg kg -1 of zinc (Zn) in its biomass and was able to tolerate high concentration of cadmium (Cd).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…It is also plant owing to its remarkable capacity to extract metal from polluted soils. The phytoremediation potential of A. mangium was been previously reported in numerous studies (Majid et al, 2012;Mohd et al, 2013). In fact, Majid et al (2012) demonstrated that A. mangium can accumulate 93.5 mg kg -1 of copper (Cu) and 79 mg kg -1 of zinc (Zn) in its biomass and was able to tolerate high concentration of cadmium (Cd).…”
Section: Introductionmentioning
confidence: 85%
“…Many studies have been conducted in this field over the last two decades, and various phytoremediation approaches (phytostabilization, phytoimmobilization and phytoextraction) have been successfully performed (Favas et al, 2019). However, the success of this new technology depends on the plant species, which must be able to tolerate and accumulate high concentrations of metals in shoots, undergo rapid growth and show high biomass production potential (Mohd et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kayu putih secara ekologi termasuk fast growing species (FGS) yang dapat digunakan untuk mempercepat proses suksesi pada lahan kritis seperti kawasan karst (Page et al, 2009) dan restorasi ekosistem gambut (Tata & Pradjadinata, 2015). Kayu putih juga dapat dikembangkan sebagai tanaman remediasi pada tanah terkontaminasi yang disebabkan oleh logam dan zat kimia (Mohd et al, 2013). Dinilai dari aspek ekonomi, kayu putih dapat dimanfaatkan sebagai material konstruksi, kayu bakar, arang, pulp, dan kayu gergajian (Alpian et al, 2013).…”
Section: Pendahuluanunclassified
“…This biological technique offers an economical and non-invasive alternative for treating polluted soils. Phytoremediation is also recognized as a green technology (Kumar et al, 1995;Huang et al, 1997;Salt et al, 1997;Blaylock et al, 1997;Vassil et al, 1998;Mohd et al, 2013) …”
Section: Introductionmentioning
confidence: 99%